The Making of Multiple Sale and Purchase Binding Agreements (PPJB) by Negligent Landowners or Developers Before Notary - Pranatia, Maria; Widjojo, Anne Gunadi Martono; Rado, Sara Novita (Notary Journal, 2024)
This study aims to analyze the role of Sale and Purchase Binding Agreement (Perjanjian Pengikatan Jual Beli/PPJB) in property transactions, particularly those conducted before a notary. PPJB is often used as a temporary binding agreement between the seller and buyer before the Sale and Purchase Deed (Akta Jual Beli/AJB) can be issued. This research uses normative juridical methods with empirical approaches to examine related regulations and their implementation in practice. The results show that while PPJB provides temporary legal certainty for both parties, legal risks remain, especially in cases of the making of multiple PPJB created by irresponsible sellers. Additionally, notary plays a crucial role in ensuring document validity and preventing disputes. The implementation of an electronic PPJB registration system at the National Land Agency (Badan Pertanahan Nasional/BPN) is proposed as a solution to enhance transparency and reduce potential future conflicts. In conclusion, PPJB can provide good legal protection if carried out carefully and transparently, supported by a strong legal system. Bahasa Indonesia Abstract: Penelitian ini bertujuan untuk menganalisis peran Perjanjian Pengikatan Jual Beli (PPJB) dalam transaksi properti, khususnya yang dilakukan di hadapan notaris. PPJB sering digunakan sebagai pengikat sementara antara penjual dan pembeli sebelum Akta Jual Beli (AJB) dapat diterbitkan. Penelitian ini menggunakan metode yuridis normatif dengan pendekatan empiris untuk menelaah regulasi yang terkait dan implementasinya dalam praktik. Hasil penelitian menunjukkan bahwa meskipun PPJB memberikan kepastian sementara kepada kedua belah pihak, masih terdapat risiko hukum terutama jika terjadi pembuatan PPJB ganda oleh pemilik tanah atau developer yang tidak bertanggung jawab di hadapan notaris. Selain itu, notaris memiliki peran krusial dalam memastikan keabsahan dokumen dan mencegah terjadinya sengketa. Penerapan sistem pendaftaran PPJB secara elektronik di Badan Pertanahan Nasional (BPN) diusulkan sebagai solusi untuk meningkatkan transparansi dan mengurangi potensi konflik di masa depan. Kesimpulannya, PPJB dapat memberikan perlindungan hukum yang baik selama dilakukan dengan hati-hati dan transparan, serta didukung oleh sistem hukum yang kuat.